A new approach for the methodology of the assessment of the predicted doses to the public of the Bryansk region in the remote period after the Chernobyl NPP accident - V. A. Yakovlev; G. Ya. Bruk (Радиационная гигиена, 2020)
This study is aimed at the evaluation of the trends of the doses from internal exposure of the adult public of the Bryansk region due to the consumption of the main dose-forming food products in the remote period after the Chernobyl NPP accident and the methodical features of the assessment of the predicted doses form the internal exposure. A new methodical approach to the calculation of the predicted doses of the public from internal exposure is based on the single exponential model of the change of the dose with a time-dependent period of a half-decrease. Results of the study allowed increasing the precision of calculation of the predicted doses to the public of the Bryansk region up to 2056. A similar method (single exponential model) can be applied for the external exposure as well. That allowed calculating predicted doses of total (external + internal) exposure. As an example, the paper includes the distribution of all settlements in the Bryansk region referred to the zones of radioactive contamination by the predicted average annual effective dose to the public and critical groups in the different time periods after the accident.